2016
DOI: 10.1177/1468018116637209
|View full text |Cite
|
Sign up to set email alerts
|

Trade agreements and labour standards clauses: Explaining labour standards developments through a qualitative comparative analysis of US free trade agreements

Abstract: Whereas a number of studies have been conducted to investigate causal relations between individual conditions (e.g. trade relations and labour standards), there is a lack of consensus among practitioners and scholars about the conditions that favour or cause labour standards improvements and, specifically, it is still unclear whether the increasing pervasiveness of Free Trade Agreements (FTAs) is conducive to enhancing labour conditions. The aim of this study is to shed light on whether labour clauses in FTAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Interviewees from the Colombian Government, the US Embassy in Colombia, and trade union representatives in Colombia agreed that this conditional approach might be more effective than the EU approach in enforcing de jure compliance with the labour rights requirements. These perceptions confirm other assessments which consider the US approach to be more effective (Giumelli and van Roozendaal, , pp. 15, 19).…”
Section: Voluntary Sustainability Standards In Colombiasupporting
confidence: 86%
“…Interviewees from the Colombian Government, the US Embassy in Colombia, and trade union representatives in Colombia agreed that this conditional approach might be more effective than the EU approach in enforcing de jure compliance with the labour rights requirements. These perceptions confirm other assessments which consider the US approach to be more effective (Giumelli and van Roozendaal, , pp. 15, 19).…”
Section: Voluntary Sustainability Standards In Colombiasupporting
confidence: 86%
“…Alongside a number of qualitative studies (e.g., ILO 2013ILO , 2016Giumelli and van Roozendaal 2017;design of LPs in PTAs. Previous studies have either used qualitative methods, preventing generalization across time and space, or focused on NTIs more broadly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been suggested that more in-depth case studies are required to identify possible effects (Giumelli & Van Roozendaal, 2016). This article, presenting an in-depth study of Korea,3 analyses the effects of a set of provisions in the agreements related to the fundamental enabling conventions in the field of freedom of association and the right to organise.…”
Section: The Korean Casementioning
confidence: 99%